CHARACTERISTICS AND STRUCTURES OF STORYTELLING TECHNIQUES IN CRIMINAL, HORROR, AND MYSTERY GENRES OF YOUTUBERS STORYTELLERS - Glenity Marchella Siauw; Lambok Hermanto Sihombing (Universitas Lambung Mangkurat, 2022)
YouTube is the biggest platform of sharing and watching online videos that enable everyone to have their own channel and upload their own contents. As YouTube attracts people’s interest, this research explores the characteristics and structure of storytelling techniques on storyteller YouTuber. This research analyzes how the storyteller YouTubers use storytelling techniques to deliver the story and how are the audience’s opinion towards the storytelling techniques of the YouTubers, focusing on three big YouTube channels, which is Nessie Judge. This research discovers the unique characteristics of each YouTuber that differentiate them one another. As the data, researcher chooses three videos of each YouTuber between January 2021 to November 2021 to analyze the storytelling techniques, audiences’ reception through the comment section and used sounds or music in the video. To answer the research questions, researcher applied three theories, which are Storytelling Theory, Audience Reception Theory and Sound Theory. The result of the research shows that these three YouTubers have their own unique characteristic that attracts the audiences’ attention to keep watching their contents.